PENGGUNAAN MICROSOFT EXCEL DI KEHIDUPAN SEHARI-HARI - Alfarisi, Dimas Hafidz; Kindi, Bilal Al; Mardatila, Aisya; Anggraeni, Reni; Wulandari, Desi (Bhakti: Jurnal Pengabdian Masyarakat, 2025)
Community Service Program (KKN) is one of the main parts of the tridharma of higher education, which requires students to play an active role in community empowerment through education, research, and service. This article discusses one of program from the KKN team from Universitas Negeri Semarang (UNNES), which took place in Tlogopucang Village, Kandangan District, Temanggung. In today's digital era, mastery of information technology has become a crucial requirement, including the ability to operate data processing applications such as Microsoft Excel. Unfortunately, many people, especially in rural areas, are still unfamiliar with the benefits of Excel. However, this application has significant benefits in everyday life, such as in household financial records, small business data management, and village administration. Therefore, the KKN team conducted a Microsoft Excel socialization activity at Junior High School (SMP) N 3 Kandangan, which aimed to introduce students to basic skills in managing data using Microsoft Excel.